2016
DOI: 10.33549/physiolres.932993
|View full text |Cite
|
Sign up to set email alerts
|

Excess of Free Fatty Acids as a Cause of Metabolic Dysfunction in Skeletal Muscle

Abstract: Obesity is often associated with metabolic impairments in peripheral tissues. Evidence suggests an excess of free fatty acids (FFA) as one factor linking obesity and related pathological conditions and the impact of FFA overload on skeletal muscle metabolism is described herein. Obesity is associated with dysfunctional adipose tissue unable to buffer the flux of dietary lipids. Resulting increased levels and fluxes of plasma FFA lead to ectopic lipid deposition and lipotoxicity. FFA accumulated in skeletal mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
72
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(77 citation statements)
references
References 111 publications
1
72
0
4
Order By: Relevance
“…High levels of palmitate have been shown to cause mitochondrial lipotoxicity, ROS production and cell death in skeletal muscle cells (Martins et al 2012;Tumova et al 2016). Interestingly, we showed that PGC-1α overexpression prevents palmitate-induced cell death, whereas UCP3 knockdown attenuated PGC-1α protective effect (Fig.…”
Section: Ucp3 Is Essential For Pgc-1α-induced Mitochondrial Functionmentioning
confidence: 68%
“…High levels of palmitate have been shown to cause mitochondrial lipotoxicity, ROS production and cell death in skeletal muscle cells (Martins et al 2012;Tumova et al 2016). Interestingly, we showed that PGC-1α overexpression prevents palmitate-induced cell death, whereas UCP3 knockdown attenuated PGC-1α protective effect (Fig.…”
Section: Ucp3 Is Essential For Pgc-1α-induced Mitochondrial Functionmentioning
confidence: 68%
“…Although some studies demonstrate that lipotoxicity‐induced apoptosis is a specific effect of saturated FFA, unsaturated FFA is also toxic in an alternative pathway, which suggests that both saturated and unsaturated FFA markedly differ in their contributions to lipotoxicity . Therefore, the combination of both types of FFAs may best reflect the physiological or pathological situation under glucolipotoxicity …”
Section: Introductionmentioning
confidence: 99%
“…A more general hypothesis of obesity effects is the lipid overflow hypothesis (Mittendorfer, 2011), which suggests that when the individual limits of physical expandability of the adipose tissue are surpassed, other tissues, e.g. skeletal or cardiac muscle, are exposed to excess free fatty acid (FFA) levels, leading to intramyocellular fat storage and mitochondrial stress due to incomplete fatty acid oxidation (Consitt et al 2009;Tumova et al 2016;Schrauwen-Hinderling et al 2016;Di Meo et al 2017). In skeletal muscle it still remains unsettled whether the observed lower ATP synthesis capacity in individuals with obesity (Bakkman et al 2010;Vijgen et al 2013) is due to a lower concentration of mitochondria, dysfunction or a combination of the two (Consitt et al 2009;Holloway et al 2009;Tumova et al 2016;Jorgensen et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…skeletal or cardiac muscle, are exposed to excess free fatty acid (FFA) levels, leading to intramyocellular fat storage and mitochondrial stress due to incomplete fatty acid oxidation (Consitt et al 2009;Tumova et al 2016;Schrauwen-Hinderling et al 2016;Di Meo et al 2017). In skeletal muscle it still remains unsettled whether the observed lower ATP synthesis capacity in individuals with obesity (Bakkman et al 2010;Vijgen et al 2013) is due to a lower concentration of mitochondria, dysfunction or a combination of the two (Consitt et al 2009;Holloway et al 2009;Tumova et al 2016;Jorgensen et al 2017). Adverse effects of obesity in skeletal muscle on the mitochondrial electron transport chain (Ritov et al 2010) and on expression of genes of the oxidative metabolism and mitochondrial biogenesis, such as the peroxisome proliferator-activated receptor γ (PPAR-γ) and PPAR co-activator 1 α (PGC-1α) (Maples et al 2015), have been reported.…”
Section: Introductionmentioning
confidence: 99%